Characterization of maize chitinase‐A, a tough allergenic molecule. Issue 9 (11th May 2017) - Volpicella, M.; Leoni, C.; Fanizza, I.; Distaso, M.; Leoni, G.; Farioli, L.; Naumann, T.; Pastorello, E.; Ceci, L. R.
Abstract: Food allergies are recognized as an increasing health concern. Proteins commonly identified as food allergens tend to have one of about 30 different biochemical activities. This leads to the assumption that food allergens must have specific structural features which causes their allergenicity. But these structural features are not completely understood. Uncovering the structural basis of allergenicity would allow improved diagnosis and therapy of allergies and would provide insights for safer food production. The availability of recombinant food allergens can accelerate their structural analysis and benefit specific studies in allergology. Plant chitinases are an example of food allergenic proteins for which structural analysis of allergenicity has only partially been reported. The recombinant maize chitinase, rChiA, was purified from Pichia pastoris extracellular medium by differential precipitation and cation exchange chromatography. Enzyme activity was evaluated by halo‐assays and microcalorimetric procedures. rChiA modeling was performed by a two‐step procedure, using the Swiss‐Model server and Modeller software. Allergenicity of rChiA was verified by immunoblot assays with sera from allergic subjects. rChiA is active in the hydrolysis of glycol chitin and tetra‐N‐acetylchitotetraose and maintains its activity at high temperatures (70°C) and low pH (pH 3). The molecule is also reactive with IgE from sera of maize‐allergic subjects. rChiA is a valuable molecule for further studies on structure‐allergenicity relationships and as a tool for diagnosing allergies.